The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1111/j.1748-1716.1990.tb08846.x
|View full text |Cite
|
Sign up to set email alerts
|

Force and EMG signal patterns during repeated bouts of concentric or eccentric muscle actions

Abstract: Healthy males (n = 14) performed three bouts of 32 unilateral, maximal voluntary concentric (CON) or eccentric (ECC) quadriceps muscle actions on separate days. Surface electromyography (EMG) of the m. vastus lateralis (VL) and m. rectus femoris (RF) and torque were measured. Integrated EMG (IEMG), mean (MPF) and median power frequencies and torque were averaged for seven separate blocks of four consecutive muscle actions. Torque was greater (P less than 0.05) for ECC than for CON muscle actions at the start o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
163
13
16

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(225 citation statements)
references
References 44 publications
31
163
13
16
Order By: Relevance
“…These data are in agreement with others who have demonstrated a 53% decrease in elbow flexors after 100 repeated eccentric actions (Linnamo, Bottas, & Komi, 2000) and repeated actions of the knee extensors (Brown, Child, Day, & Donnelly, 1997;MacIntyre, Reid, Lyster, Szasz, & McKenzie, 1996). However, others have shown that repeated eccentric muscle actions are extremely fatigue resistant despite high force production (Emery et al, 1994;Hortobagyi et al, 1996;Tesch, 1990 It has been suggested that an ICC of 0.88 or above and CV not exceeding ± 6% demonstrates good reliability in isokinetic strength testing (Gleeson & Mercer, 1996). The relative reliability for the WFI and TFI in the current study are lower than this recommended value for both the knee extensors and flexors.…”
Section: Discussionsupporting
confidence: 82%
“…These data are in agreement with others who have demonstrated a 53% decrease in elbow flexors after 100 repeated eccentric actions (Linnamo, Bottas, & Komi, 2000) and repeated actions of the knee extensors (Brown, Child, Day, & Donnelly, 1997;MacIntyre, Reid, Lyster, Szasz, & McKenzie, 1996). However, others have shown that repeated eccentric muscle actions are extremely fatigue resistant despite high force production (Emery et al, 1994;Hortobagyi et al, 1996;Tesch, 1990 It has been suggested that an ICC of 0.88 or above and CV not exceeding ± 6% demonstrates good reliability in isokinetic strength testing (Gleeson & Mercer, 1996). The relative reliability for the WFI and TFI in the current study are lower than this recommended value for both the knee extensors and flexors.…”
Section: Discussionsupporting
confidence: 82%
“…The aEMG and MPF values for all 6 sections were then calculated and used for analysis. Previous authors [42][43][44] reported increased aEMG amplitude and decreased MPF (spectral compression) associated with both isotonic and dynamic muscular contractions in a fatigued state. Third, fatigue has been defined as a reduction in the force-generating capacity of the neuromuscular system that occurs during sustained activity.…”
Section: Data Collectionmentioning
confidence: 99%
“…17 The reduced surface electromyographic (EMG) activity of muscles performing eccentric actions is consistent with the postulated superiority of the mechanical efficiency of these muscle contractions. 18 The intensity of the muscle contraction seems to be an important stimulus for muscle growth and strength development, 19 and, therefore, the greater capacity of eccentric actions to produce force has received the attention of many investigators, who have explored the effectiveness of eccentric exercise regimens in enhancing skeletal muscle performance. 20 Although muscle adaptations observed after training tend to be contractionspecific, 21,22 it is generally accepted that exercise protocols in which eccentric actions are emphasized produce more important gains in strength, 23,24 muscle mass 25,26 and neural adaptations 27,28 than regimens consisting of concentric actions only.…”
Section: Introductionmentioning
confidence: 99%